Analisis Perbandingan Pusat Kreativitas UMKM dengan Penerapan Arsitektur Metafora - Rangkuti, Zhafira Hafiza; Fachrudin, Hilma Tamiami (Universitas Medan Area, 2024)
The UMKM Creativity Center is a place to support the development of Micro, Small, and Medium Enterprises (MSMEs). The UMKM Center has an important role in creating an environment that inspires and supports the growth of the micro, small, and medium enterprise (MSME) sector. By analyzing the concept, space, and form applied to the UMKM building, this research aims to explore and understand the impact and effectiveness of the physical design of the UMKM Creativity center that adopts the metaphor architecture theme. The research method used uses a qualitative method with data collection that is analyzed descriptively. This method involves collecting and analyzing written sources or literature relevant to the research topic. Literature study by conducting a comparative study of 3 buildings with the function of the UMKM creativity center and 3 buildings that apply metaphor architecture. The research found that the appropriate type and form of space is needed to support the success of the UMKM creativity center building with the application of metaphor architecture. Metaphor as a building expression and identity at the UMKM Center through forms that help increase the sense of creativity of MSME players to create the newest innovations.